Pengaruh Gaya Kepemimpinan Transformasional Dan Transaksional Terhadap Kinerja Pegawai Departemen SDM PT. SEMEN GRESIK (Persero) Tbk - Fanni Adhistya Italiani (BISMA (Bisnis dan Manajemen), 2018)
PT. Semen Gresik (Persero) Tbk. is to be the most superior andalways grown up in Asia. The leader is a must to adjusting with the organisations environment, the relations between the leader, human resources departement and the employee has good relationship, so that each can perform the role, tasks, and function.This research is using methods of qualitative approach. The sample technique is using purposive sampling. Sample satures is sample determination techniques when all members of the population used as sample. This is often to implemented when the population is relatively small, less than 30 people, or research want to make very small generalization error. Analyze technique is using multiple regression linear. The results on this research is the transformational leadership has a positive and sifnificant effect to employee peformance and the transactional leadership has a positive and significant effect to employee performance human resourcing